Managing boron deficiency in vegetable crops - Tiwari, KN; Tiwari, Rakesh (Indian Horticulture, 2015)
Boron deficiency is being increasingly observed in vegetables and fruit crops in alkaline/calcareous, coarsetextured and low organic matter soils and acid soils. Characteristic symptoms are invariably seen. Therefore, diagnosis and correction of B deficiency in important vegetable crops grown in India in a wide range of soils is the need of the hour to increase their production.